Psychophysiology and Neuroscience in Sport: Introduction - Zaichkowsky, L. (Journal of Clinical Sport Psychology, 2012)
While clinical psychology has embraced the importance of psychophysiology and neuroscience when considering the client condition, the field of sport psychology has been slower to consider the potential importance of this area for athletic clientele. Therefore, this special issue of the Journal of Clinical Sport Psychology was conceptualized and constructed to describe the current state of psychophysiological and neuroscience research and illustrate how clinical sport psychologists may, in the future, use technologies such as biofeedback/neurofeedback and physiological measurement (EMG, EEG, skin temperature, EDR, HR, HRV, respiration, and hormonal responses) with high-level athletes from a variety of sports for both performance enhancement and diagnosis and management of head injury. As Guest Editor of this unique special issue, I have written the present introduction to highlight the issue`s important mission. This introductory paper sets the stage for five informative and cutting-edge articles by leading professionals. In all, the articles cover an array of topics on psychophysiology and neuroscience in sport, such as (a) the theoretical underpinnings of biofeedback/neurofeedback,